WHAT DOES PROVIDE A CLINICAL EFFICACY OF METOPROLOL? - E. V. Kuleshova (Рациональная фармакотерапия в кардиологии)
Relationship of metoprolol clinical efficacy with its different salts (tartrate, succinate, fumarate) as well as its presentations (tablets with immediate, controlled or sustained release) is analyzed. It is highlighted that pharmacodynamic properties depend on metoprolol molecule only. These properties do not change after modification of drug presentation or metoprolol plasma concentration which depends on velocity of drug release from the tablet. Data of randomized clinical trials are discussed in regard to development of evidence base for use of different metoprolol presentations in treatment of patients with arterial hypertension, unstable angina, myocardial infarction, heart failure. Indications for tartrate and succinate salts of metoprolol are presented. Results of clinical studies on efficacy of metoprolol tartrate in long-acting drug presentations are analyzed.